Islamic finance and economic growth: The Turkish experiment - Mohammed Ayoub Ledhem; Mohammed Mekidiche (ISRA International Journal of Islamic Finance, 2022)
Purpose - This study aims to empirically investigate the connection between Islamic finance and economic growth in Turkey using the endogenous growth model. Design/methodology/approach - It applies quantile regression with the Markov chain marginal bootstrap resampling technique by adopting total Islamic financing as the main exogenous explanatory factor in the endogenous growth model, while the gross domestic product (GDP) is employed as a measure of economic growth. The sample consists of all full-fledged participation (Islamic) banks operating in Turkey spanning from 2013Q4 until 2019Q4. The study uses academic literature, official financial reports from the Participation Banks Association of Turkey, REDmoney Group, Islamic Financial Services Board (IFSB) and the International Monetary Fund (IMF) database. Findings - The results show that Islamic finance is promoting economic growth in Turkey, which mirrors the success of the New Turkish Economy Program (2019-2021) which aims at boosting economic growth by enhancing the Islamic finance share in the Turkish banking sector and the global market. Research limitations/implications - Turkey has a dual banking system (conventional and participation (Islamic)) and both can influence the country's real economy. This study is limited to the influence of Islamic banking on Turkish economic growth. The study also restricts its size and coverage from 2013Q4 to 2019Q4, to cover the years over which data for all variables included in the research are available. Practical implications - This paper suggests the adoption of the Turkish successful experiment as a path to reach economic growth by increasing the Islamic finance share in the banking industry for countries that seek to promote economic growth by Islamic finance, as the findings of this paper support. Originality/value - This study is the first that examines the influence of Islamic finance on economic growth under a new theoretical framework of the endogenous growth model in Turkey using a robust non-parametric approach.
Keywords: 330; Economic growth; Endogenous growth model; Islamic finance; Markov chain marginal bootstrap quantile regression; Non-parametric approach; Participation banks